O cabra do Cariri Cearense: a invenção de um conceito oitocentista - Cortez, Ana Sara Ribeiro Parente (2015)
The transformation of a word into a concept - Cabra, having a space and a time reference, those being the Cariri region in the state of Ceará and the nineteenth century, is the object of this research. The focus is to investigate how, in many ways and different at various times of the nineteenth century, a negative identification for a category was created, the colored workers of the Cariri region, whether these were free workers, freed former slaves, or slaves. In a broader context, this construction is the result of the time in which it was tried to define content for the Brazilian nation, especially in the definition of what was a national citizen. As this identity was formed, on the other hand, an anti-definition of citizen was also constructed, which encompassed those who did not correspond to the legal and financial parameters established by the Brazilian noble elite in the nineteenth century. In the southern region of Ceará, this definition was associated with individuals or even to the group, called cabras. Initially associated with a phenotype and the legal status of the slave, to which other features were subsequently aggregated, such as being rural workers, henchmen, among others, the cabra was crystallized as a category of social classification: associated with men of color, workers subject to a master. The tensions related to the movement of this definition is not restricted to the moment of formation of the Brazilian nation, not even to the eighteen hundreds, insofar as the "invention of the cabra" reverberated in the literature of the twentieth century on the past, highlighting the concept of cabra as an indicator not only of the characteristics of the historical moment, but also to delimit the vision of the past, a central element in the discursive formulation of the identity of the Cariri region by intellectuals imbued with this task in the last century.